Cytokinin Production by Azospirillum brasilense Contributes to Increase in Growth, Yield, Antioxidant, and Physiological Systems of Wheat (Triticum aestivum L.) - Zaheer, Muhammad Saqlain; Ali, Hafiz Haider; Iqbal, Muhammad Arslan; Erinle, Kehinde O.; Javed, Talha; Iqbal, Javaid; Hashmi, Makhdoom Ibad Ullah; Mumtaz, Muhammad Zahid; Salama, Ehab A. A.; Kalaji, Hazem M.; Wróbel, Jacek; Dessoky, Eldessoky S. (Frontiers in Microbiology, 2022)
Plant growth promoting rhizobacteria are known to associate with several cereal crops. The rhizobacterium exerts its function through synthesis of diverse arrays of phytohormones including cytokinin (Ck). However, it is difficult to determine the plant growth promotion where a bacterium produces many different kinds of phytohormones. Therefore, to determine the involvement of cytokinin in growth promotion and activation of antioxidant and physiological systems, we arranged this experiment. Wheat seeds (Triticum aestivum L.) were inoculated with A. brasilense RA-17 (which produces zeatin type cytokinin) and RA-18 (which failed to produce cytokinin). Results showed that seed inoculation with RA-17 significantly improved growth and yield related parameters, compared to RA-18. Activity of enzymes, proline contents and endogenous hormonal levels in wheat kernels were significantly improved with RA-17 than RA-18. Strain RA-17 enhanced assimilates in grains than strain RA-18 resulting to higher crop yield. These results suggest that microbial cytokinin production may be necessary for stimulation of plant growth promotion, activation of antioxidant and physiological systems in wheat.